2008
DOI: 10.1016/j.ecoenv.2007.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metals in mosquito larval habitats in urban Kisumu and Malindi, Kenya, and their impact

Abstract: Concentrations and distribution of cadmium, chromium, copper, iron, lead, manganese and zinc in mosquito larval habitats in urban Kisumu and Malindi, Kenya and their effect on the presence of Anopheles gambiae, Aedes aegypti, Culex quinquefasciatus and Anopheles funestus larvae were investigated. Manganese and iron were the most prevalent heavy metals in water of larval habitats in urban Kisumu and Malindi, respectively. Iron was the most prevalent heavy metal in bottom sediments in larval habitats in both cit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 22 publications
4
51
1
Order By: Relevance
“…gambiae s.l. complex occur in polluted urban larval habitats in Dar-es-Salaam [72], Kisumu, and Malindi [73]. These geographical differences outline the fact that adaptation to urban pollution is happening repeatedly and independently within the species complex, and it is presumably very recent given that urbanization is a relatively novel phenomenon; furthermore, they suggest that lineage splitting between the M and S forms predates adaptation to uban habitats, in agreement with the estimated age of their divergence that is situated well before the Neolithic revolution [74].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…gambiae s.l. complex occur in polluted urban larval habitats in Dar-es-Salaam [72], Kisumu, and Malindi [73]. These geographical differences outline the fact that adaptation to urban pollution is happening repeatedly and independently within the species complex, and it is presumably very recent given that urbanization is a relatively novel phenomenon; furthermore, they suggest that lineage splitting between the M and S forms predates adaptation to uban habitats, in agreement with the estimated age of their divergence that is situated well before the Neolithic revolution [74].…”
Section: Discussionmentioning
confidence: 99%
“…Further, it is possible that local adaptation may be associated to differential responses not only to nitrogenous compounds, but also to other environmental stressors characteristic of An. gambiae breeding sites [57,72,73,78,79], like temperature, organic and inorganic suspended solids, dissolved substances, emulsions and colloids (including e.g. heavy metals, detergents, oils, or other kinds of nutrients), or biological factors like micro-organisms [80], competitors [81-83], predators [35,84], and their interactions (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Controlling mosquito larvae in cess pits and house drainages has been difficult for a number of reasons such as variable and unexpected amount of water and water quality, flushing and dilution of the bioinsecticide, organic pollution, and accumulations of debris (Su et al 2003;Su 2008). Larval habitats in urban Malindi have been found to contain relatively high concentrations of heavy metals such as chromium, copper, iron, lead, manganese, and zinc (Mireji et al 2007). It has been shown that a decrease in pH, an increase in water temperatures and the dilution effect directly affect the activity of Bti/Bs (Mulla et al 1990).…”
Section: Habitat Type Early Instars Late Instars Early Instars Late Imentioning
confidence: 98%
“…Absence of favorable mosquito larval habitats in urban environments has been associated with reduction in mosquito species diversity (Chinery, 1984; Trape and Zoulani, 1987; Coene, 1993; Coluzzi, 1993; Chinery, 1995). The species that succeed in these environments encounter a variety of larval habitats, some of which may be highly polluted with domestic and industrial sewage (Sattler et al, 2005; Awolola et al, 2007; Djouaka et al, 2007), and heavy metals (Mireji et al, 2008). Understanding the effects of environmental pollutants and responses of Anopheles mosquitoes is important for elucidating any adaptive changes that may take place and how these affect their population dynamics and vectorial capacity.…”
Section: Introductionmentioning
confidence: 99%